The Complexity of Sleep Disorders in Children with FASD - Więcko, Laura; Trela, Katarzyna; Tuteja , Aleksander; Olczyk, Liwia; Podleśna, Daria; Gęborys, Kamila; Burzykowska, Klaudia (Quality in Sport, 2025)
Introduction and Purpose: Fetal alcohol spectrum disorders (FASD) is a group of conditions that can occur after prenatal alcohol exposure. In recent years, it is estimated that about 10% of women consume alcohol during pregnancy. The aim of this study is to draw attention to sleep quality in children with FASD and highlight the need for implementing appropriate diagnostic and therapeutic strategies that can improve their overall functioning and quality of life. Methods and Materials: This article is based on a review of scientific literature from PubMed and other databases, mainly from the years 2020 to 2025. The following keywords were used: “fetal alcohol syndrome”, “fetal alcohol spectrum disorder”, “sleep disturbances” and “prenatal alcohol exposure”. Conclusion: The clinical manifestations of FASD are highly complex and affect all organ systems. Poor sleep hygiene in children with FASD has a significant impact on multiple areas of life, often leading to additional dysfunctions. Elevated emotional distress, difficulties with emotional regulation and cognitive impairments are closely associated with reduced sleep quality. While several validated tools are available to assist in the diagnosis of sleep disorders, the treatment of FASD symptoms remains more complex and is primarily focused on symptom management. Importantly, the most effective approach remains prevention — namely, complete abstinence from alcohol during pregnancy.